EVOLUTION OF NEOCONSERVATIZM IDEOLOGY AND ITS POLICY - Авксентьєв, А.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article is devoted to the analysis of neoconservatism phenomenon in abstract-ideological and practical-political dimensions. The special attention is focused to the evolution of neoconservatism movement, problems of ideological succession of neoconservatism, to the basic ideological principles and characteristic features of political course. They are making conclusions concerning the character of ideological principles, chronologic and territorial limits of dissemination, and also prospects of neoconservatism.